Translation Shifts Found in the Translation of Merry Riana: Mimpi Sejuta Dolar Novel by Alberthiene Endah into Million Dollar Dream - Djamaleng, Riskayani; Gede Ayu Dhyana Paramita, Luh; Wayan Budiarta, I; Made Susini, Ni (KnE Social Sciences, 2022)
It has been considered that translation is the process of transferring a message or meaning from a language to the other. Thus, this research was proposed to analyze the translation shift in a Novel. The data of this paper were taken from an Indonesian novel entitled Merry Riana: Mimpi Sejuta Dolar by Alberthiene Endah (2011) and the English translation entitled Million Dollar Dream translated by Maggie Tiojakin (2016). The analysis was mainly aimed at finding out the types of translation shifts found in these two novels. The main theory used was taken from a book entitled A Linguistic Theory of Translation by Catford (1965). The other theories were also applied in this research. There were some steps done in collecting data observation. When the data were the method used in analyzing the data was a descriptive method with an informal technique of presentation. It was found that there were two major types of shifts. They were level shifts and category shifts. The category shifts involved structure shift, class shift, unit/ rank shift and intra-system shift. The result of this research showed that the translation shifts most commonly found is in the category shifts include structure shift, class shift, unit/ rank shift and intra-system shift. Commonly, shifts in the translation were caused by the different structure of the source language and the target language and every language has its own form to convey the meaning. Keywords: translation shift, novel, translation